The Existence of Bale Kerta Adhyaksa as an Instrument for Resolving General Legal Cases in Bali - I Nyoman Sumardika; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti; Anak Agung Ngurah Adhi Wibisana (Fakultas Hukum, Universitas Warmadewa, 2025)
The paper entitled “The Existence of Bale Kerta Adhyaksa as an Instrument for Resolving General Legal Cases in Bali” was prepared in connection with the enactment of the Draft Regional Regulation of the Province of Bali concerning Bale Kerta Adhyaksa into a Regional Regulation, which will take effect following the implementation of Law Number 1 of 2023 on the Criminal Code on 2 January 2026. This paper examines and discusses two legal issues relevant to the existence of Bale Kerta Adhyaksa, namely: (1) the authority of Bale Kerta Adhyaksa in Bali, and (2) the scope of the substantive provisions of the Regional Regulation on Bale Kerta Adhyaksa in Bali. The writing method is grounded in the doctrine of legislative law, thereby adopting a normative research type which utilizes normative or non-empirical research materials with a statutory approach and a conceptual approach, drawing from both primary and secondary legal materials. The analysis employs the concept of regulatory impact assessment and consistency analysis, applied both at the stage when the regulation was still in draft form and after its stipulation as a Regional Regulation of Bali Province. This analysis is carried out using systematic interpretation through inductive and deductive reasoning, presented in a structured and coherent manner. The authority of Bale Kerta Adhyaksa in Bali is to resolve general legal cases occurring within the jurisdiction of customary villages. Institutionally, it is expected to resolve cases by prioritizing a win–win solution, particularly for minor criminal cases and minor civil cases. Meanwhile, the scope of the substantive content of the Regional Regulation on Bale Kerta Adhyaksa in Bali includes the realization of an effective, efficient, comprehensive, and conclusive system for resolving general legal cases, as well as the reduction of the frequency of minor criminal and civil cases within customary villages areas. The formulation of case resolution is embodied in the form of a “Peace Statement Letter or Deed” and a “Peace Agreement Letter or Deed”, which are recorded in a mutual agreement between the parties, signed by them, and must be carried out in good faith. The decisions are final and binding.